Crisis management during anaesthesia: anaphylaxis and allergy. Issue 3 (2nd June 2005) - Currie, M; Kerridge, R K; Bacon, A K; Williamson, J A
Abstract : Background: Anaphylactic and anaphylactoid reactions during anaesthesia are a major cause for concern for anaesthetists. However, as individual practitioners encounter such events so rarely, the rapidity with which the diagnosis is made and appropriate management instituted varies considerably. Objectives: To examine the role of a previously described core algorithm "COVER ABCD–A SWIFT CHECK", supplemented by a specific sub-algorithm for anaphylaxis, in the management of severe allergic reactions occurring in association with anaesthesia. Methods: The potential performance of this structured approach for each of the relevant incidents among the first 4000 reported to the Australian Incident Monitoring Study (AIMS) was compared with the actual performance as reported by the anaesthetists involved. Results: There were 148 allergic reactions among the first 4000 incidents reported to AIMS. It was considered that, properly applied, the structured approach would have led to a quicker and/or better resolution of the problem in 30% of cases, and would not have caused harm had it been applied in all of them. Conclusion: An increased awareness of the diverse clinical manifestations of allergy seen in anaesthetic practice, together with the adoption of a structured approach to management should improve and standardise the treatment and improve follow up of patients suspected of having suffered a significant allergic reaction under anaesthesia.